2013
DOI: 10.1371/journal.pone.0061286
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Genetic Anticipation in Lynch Syndrome

Abstract: Telomere length variation has been associated with increased risk of several types of tumors, and telomere shortening, with genetic anticipation in a number of genetic diseases including hereditary cancer syndromes. No conclusive studies have been performed for Lynch syndrome, a hereditary colorectal cancer syndrome caused by germline mutations in the DNA mismatch repair genes. Here we evaluate telomere length in Lynch syndrome, both as a cancer risk factor and as a mechanism associated with anticipation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
2
25
1
Order By: Relevance
“…To date, anticipation has been found in two types of hereditary diseases, neurologic diseases such as fragile X syndrome, X-linked spinal and bulbar muscular atrophy, myotonic dystrophy and Huntington disease, and hereditary cancer syndromes such as dyskeratosis congenita, hereditary breast cancer, Li-Fraumeni syndrome, and hereditary nonpolyposis colorectal cancer syndrome (Lynch syndrome). Two molecular changes may be involved in the anticipation, expanding of trinucleotide repeats found in the anticipation in neurologic diseases, and shortening of telomere detected in the anticipation of hereditary cancer syndromes (13)(14)(15)(16)(17)(18)(19)(20)(21). The gradual decrease of telomere length with aging is attributed to the decrease of telomerase function or mutations accumulated in the DNA repair system besides aging (22).…”
Section: Introductionmentioning
confidence: 99%
“…To date, anticipation has been found in two types of hereditary diseases, neurologic diseases such as fragile X syndrome, X-linked spinal and bulbar muscular atrophy, myotonic dystrophy and Huntington disease, and hereditary cancer syndromes such as dyskeratosis congenita, hereditary breast cancer, Li-Fraumeni syndrome, and hereditary nonpolyposis colorectal cancer syndrome (Lynch syndrome). Two molecular changes may be involved in the anticipation, expanding of trinucleotide repeats found in the anticipation in neurologic diseases, and shortening of telomere detected in the anticipation of hereditary cancer syndromes (13)(14)(15)(16)(17)(18)(19)(20)(21). The gradual decrease of telomere length with aging is attributed to the decrease of telomerase function or mutations accumulated in the DNA repair system besides aging (22).…”
Section: Introductionmentioning
confidence: 99%
“…The results were compared to the results we published in a previous study of 144 cancer-affected MMR gene mutation carriers, 100 unaffected MMR gene mutation carriers and 234 controls [16].…”
Section: Resultsmentioning
confidence: 93%
“…Regarding hereditary CRC, our group recently reported that cancer-affected MMR gene mutation carriers had shorter telomeres and showed faster telomere attrition with age, measured in blood, than controls and cancer-free MMR gene mutation carriers [16]. Nevertheless, the role of telomere length as cancer risk modifier in LS could not be asserted since it had been argued that the shortened telomeres observed in retrospectively collected samples from cancer-affected individuals might be a consequence of the disease [8], [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Lynch syndrome families shows that telomere lengths in leukocytes of cancer patients carrying MMR gene mutations are significantly shorter than symptom-free mutation carriers and healthy controls [84]. In addition, cancer patients with MMR gene mutations show the most pronounced telomere attrition with age [84]. However, it is entirely unknown whether the shorter telomere length in cancer patients reflects the effects of MMR deficiency or merely represents a consequence of the cancer syndrome.…”
Section: Mmr At Telomeresmentioning
confidence: 99%